STRATEGI PENDIDIKAN PAUD DALAM MENANAMKAN AKHLAK MULIA MELALUI PEMBIASAAN DOA DAN HAFALAN SURAT PENDEK (STUDI KASUS DI BA KETRO 1) - Ika Nur Hasanah; Tentiasih, Septyana (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
This study aims to analyze the strategies used by Early Childhood Education (PAUD) in instilling noble moral values through the habituation of daily prayers and memorization of short Quranic verses, with a case study at BA Ketro 1. This research employs a descriptive qualitative method with a case study approach. Data were collected through observations, semi-structured interviews with teachers and parents, as well as documentation related to the habituation activities conducted at the school. The results of the study indicate that the habituation of prayers and memorization of short verses is implemented in a structured manner, utilizing creative media such as songs, games, and visualizations, designed according to the characteristics of young children. Furthermore, collaboration between teachers, parents, and the community is a key factor in supporting the success of this habituation program. This research makes an important contribution to the development of character education strategies in Islamic-based PAUD institutions, especially in rural areas with distinct socio-cultural potentials. Keywords:  Early Childhood Education, Noble Character, Daily Prayers, Memorization of Short Surahs